Pengaruh Profitabilitas, Likuiditas, dan Leverage Terhadap Nilai Perusahaan Energi Baru Terbarukan - Salsabilla, Marcella; Diana, Nana (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study was to determine and analyze financial performance as measured by the ratio of profitability, liquidity, leverage and stock price. by profitability, liquidity, leverage and stock price ratios. The research was conducted at companies that produce New Renewable energy listed on the Indonesia Stock Exchange. The research method used is descriptive analysis with the data used is secondary data in the form of Profit and Loss Financial statements and Financial Position Reports on companies that produce New Renewable Energy listed on the Indonesia Stock Exchange. The analysis tool uses financial ratios in the form of Return on Asset (ROA), Current Ratio (CR), Debt to Equity Ratio (DER) and Price to Book Value (PBV). This research was conducted on 4 companies that produce New Renewable Energy listed on the Indonesia Stock Exchange in 2020-2022. Quantitative methods were used in this study. Multiple linear regression and descriptive analysis are the methods used in this study. The results of this study show that profitability has a positive effect on the value of companies that produce New Renewable Energy, Liquidity has a positive effect on the value of companies that produce New Renewable Energy, and Leverage has no effect on companies that produce New Renewable Energy.